Effects of different physical parameters on the stability of anthocyanin from coconut (Cocos nucifera) husk (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Anthocyanin, a bioactive compound present in plants, possesses the characteristic of being an extractable pigment. Due to its bioavailability and wide spectrum of colors, extensive research has been conducted on anthocyanin to explore its medicinal advantages and its potential as a natural coloring agent. However, it is reported to be easily degraded by external environmental factors due to its high reactivity. The husk from coconut (Cocos nucifera) has been proven to contain a significant amount of anthocyanin. Therefore, this study aims to evaluate the effects of temperature, autoclaving condition, pH, and light on the stability of anthocyanin from coconut husk. The anthocyanin extracted from the mesocarps of brown coconut husks was tested at different temperatures (50 ? to 70?), pH (1 to 14), autoclaving conditions (15 minutes to 60 minutes), and light exposure (room temperature for 70 days). In extreme temperatures and long durations of autoclaving conditions, anthocyanin extracts were slightly degraded in terms of colour strength and total anthocyanin content. The acidity and alkalinity of the samples affected the stability of anthocyanin extracts drastically. The colour strength and total anthocyanin content steadily increased as the pH rose. Light exposure also influenced the stability of anthocyanin extract throughout the 70-day exposure to fluorescent light. To sum up, anthocyanin extracts from the C. nucifera are stable in a highly alkaline condition and must be stored away from light, extreme heat, and high pressure.
Keywords: anthocyanin; coconut; dye; husk; pigment